Tindak Pidana Kesusilaan Pada Retardasi Mental : Kasus yang belum terjangkau oleh hukum (Laporan Kasus) - Basbeth, Ferryal; Kristanto, Erwin; -, Irmansyah; Satriyo, Rudy (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2008)
A woman, MK (24), was taken to PKT RSCM by her parents with a visum application letter fromthe police which states that a perpetrator is suspected for sexual harassment according to article 285. Duringthe examination, an old tear was found. Sperm examination was not conducted because the intercourse hadhappened more than three days before the examination. Through anamnesis, the victim confessed to havinghad sex without being forced or threatened. About 10 days later the victim’s parents returned to PKT RSCMand asked to have the anamnesis part of the Visum changed into a statement that the victim was being forcedand threatened. Previously, the article that the investigator accused, article 285 on raping, is changed intoarticle 335 on unpleasant act which made the victim’s family unsatisfied. Furthermore, the family alsoshowed a psychiatric test result stating that the victim suffers from mental retardation. This case cannot beclassified into article 285 because there is no threat and violence. Nor can it be classified into UUPKDRTbecause the perpetrator is not a family member. The case also cannot be covered by the bill of child protectionbecause the victim is 24 years old. The paper will discuss the medicolegal aspects on the mentally retardedvictim and how far the mentally retarded victim can give consent for intercourse.
Keywords: mental retardation, consent, legal aspect